Individualizing Intervention to Teach Joint Attention, Requesting, and Social Referencing to Children with Autism - Weisberg, Holly R. (Behav Anal Pract, 2018)
Social communication skills such as joint attention (JA), requesting, and social referencing (SR) are deficits in children with autism spectrum disorder (ASD). Shifting gaze is a common response across these skills. In many studies, children respond variably to intervention, resulting in modifications to planned intervention procedures. In this study, we attempted to replicate the procedures of Krstovska-Guerrero and Jones (Journal of Developmental and Physical Disabilities 28; 289–316, 2016) and Muzammal and Jones (Journal of Developmental and Physical Disabilities 29; 203–221, 2017) to teach JA, requesting, and SR. In general, intervention procedures consisting of prompting and reinforcement were effective in teaching requesting, SR, and JA skills to children with ASD. However, not all children acquired each skill, and all children required individualized procedures to acquire some skills. We report the process of deciding how to modify intervention and discuss considerations for practitioners when planning intervention that may improve children’s performance.